Venituri şi performanţă în politica socială - Ilie, Simona (Calitatea Vieții, 2017)
The article observes the dynamic of poverty by stages of households’ income formation and by groups. Based on data from 2013–2015, the study lays out indicators of poverty and inequality in Romania compared to European countries, grouped by the social models outlined by Boeri in early 2000. Rarely approached in comparative studies, the structure of household budgets in several European countries is a preamble of the analysis. The conclusions of the analysis lead to the formulation of possible intervention directions to increase the performance of the Romanian social policy.